2009
DOI: 10.1101/cshperspect.a001073
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p53 Gene Family in Reproduction

Abstract: The p53 family of genes ( p53, p63, and p73) is conserved over evolutionary time scales. Although the functions of p53 gene and its protein as a tumor suppressor have been firmly established, the earliest functions for the p53 ancestral genes in worms and flies are to ensure germ-line genomic integrity and the fidelity of the developmental process. In vertebrates, the p53 family of genes retains those functions in germ-line genomic integrity but have added important functions in regulation of reproduction. Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 71 publications
0
58
1
Order By: Relevance
“…However, recent data suggest that TP53 does not act merely as a death signal, but rather as a modulator of damage responses to ensure successful development (Toyoshima 2009). It has been suggested that the primordial function of the TP53 ancestor gene was to ensure fecundity and production of normal offspring and that its function as a tumour suppressor came later in evolution (Hu 2009). Accordingly, there is evidence indicating that expression of TP53 is essential for female fertility (Hu et al 2007) and that active TP53-dependent cell death signalling is required to suppress erroneous replication of damaged DNA during the preimplantation period (Toyoshima 2009) and to avoid abnormalities during foetal development (Torchinsky & Toder 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggest that TP53 does not act merely as a death signal, but rather as a modulator of damage responses to ensure successful development (Toyoshima 2009). It has been suggested that the primordial function of the TP53 ancestor gene was to ensure fecundity and production of normal offspring and that its function as a tumour suppressor came later in evolution (Hu 2009). Accordingly, there is evidence indicating that expression of TP53 is essential for female fertility (Hu et al 2007) and that active TP53-dependent cell death signalling is required to suppress erroneous replication of damaged DNA during the preimplantation period (Toyoshima 2009) and to avoid abnormalities during foetal development (Torchinsky & Toder 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the inactivation of p53 is not the primary cause of aneuploidy, its dysfunction strongly facilitates a tolerance to this chromosomal instability [5] and, 2) Loss of p73 function due to polymorphisms in its encoding gene may interfere in the control of the meiotic spindle during oogenesis, increasing the risk of aneuploidy in the offspring [56,57]. The expression of TP73 naturally decreases with age, therefore the loss of TP73 function may contribute to the increase of aneuploidy produced by old oocytes [26,56,57]. In our sample about 43% of women were younger than 35 years at the time of the trisomic fetus conception.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown the important role played by p53 family as regulators of crucial processes related to human reproduction [14,26]. Our working hypothesis was based on two main pieces of evidence: 1) The loss of p53 function or genes that regulate this metabolic pathway may be related to the accumulation of aneuploid cells, increasing the risk of DS birth in women with these polymorphisms [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies have shown that p53 and its family members, including p63 and p73, all play important roles in reproduction. [10][11][12][13] Recent studies have also suggested that p53 plays a role as a longevity regulator. It has been well established that p53 has a profound impact on longevity in different organisms through its tumor-suppressive function.…”
Section: Introductionmentioning
confidence: 99%